ANALISIS YURIDIS TENTANG KONSEP HAK MENGUASAI NEGARA SUMBER DAYA ALAM DI LAUT DALAM WILAYAH HUKUM INDONESIA - Akhmad Zulkifli (Belom Bahadat, 2019)
This study analyzes the concept of the right to control the State of natural resources at sea in the jurisdiction of Indonesia. The purpose of this legal research is to find out about the concept of the right to control the state according to the 1945 Constitution of the Republic of Indonesia and who has the authority to manage and utilize natural resources at sea in the framework of the state's right to control. To analyze the legal problems mentioned above, then the type of normative legal research is used, namely research on literature materials or relevant secondary data. This research uses the statutory approach and the concept approach. Then this research is analytical descriptive. The legal materials used consist of primary, secondary and tertiary legal materials. The legal materials are collected through literature study. The legal materials that have been collected are processed through the stages of examination, marking, reconstruction and systematic. Then analyzed qualitatively. The results of the research show that first, the concept of the state's right to control natural resources at sea in the Indonesian jurisdiction according to the 1945 Constitution of the Republic of Indonesia contains the understanding that the state as the highest people's power organization holds the power to control and authorize these natural resources which intended for the maximum prosperity of the people in accordance with the provisions of Article 33 paragraph (3) of the 1945 Constitution. Second, both the central government based on the authority of attribution and the regional (provincial) government based on the authority of the delegation has the authority to manage and utilize natural resources at sea in the jurisdiction Indonesia is in accordance with the applicable laws and regulations.